2008
DOI: 10.1007/s10551-008-9671-x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Ethics in Japan: An Economic Reconstruction of Moral Agency of Japanese Firms – Qualitative Insights from Grocery/Retail Markets

Abstract: The paper reconstructs in economic terms managerial business ethics perceptions in the Japanese consumer market for fast moving, daily consumption products. An economic, three-level model of moral agency was applied that distinguishes unintentional moral agency, passive intentional moral agency, and active intentional moral agency. The study took a qualitative approach and utilized as empirical research design an interview procedure. The study found that moral agency of Japanese firms mostly extended up to uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…Gowri () put forth four techniques to use when analyzing ethical business decisions involving harm: identification, evaluation of use, evaluation of the effect of proliferation, and evaluation of consequences. Additionally, the ethical responsibility of firms (Wagner‐Tsukamoto, ) were studied, as well as approaches to moral problems (Vartiainen, ) and moral agency.…”
Section: Discussion Of Major Thematic Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gowri () put forth four techniques to use when analyzing ethical business decisions involving harm: identification, evaluation of use, evaluation of the effect of proliferation, and evaluation of consequences. Additionally, the ethical responsibility of firms (Wagner‐Tsukamoto, ) were studied, as well as approaches to moral problems (Vartiainen, ) and moral agency.…”
Section: Discussion Of Major Thematic Findingsmentioning
confidence: 99%
“…In particular, the role of sensemaking by giving meaning to experience was utilized in several studies (Cramer et al ., ; Sonenshein, ; Reis, ), highlighting an interesting avenue for business ethics research. Other insightful views included moral agency and problem identification (Vartiainen, ; Wagner‐Tsukamoto, ), and the role of technology (Alexander & Nicholls, ; Svensson & Bååth, ; Light & McGrath, ; Somogyvári, ; Strider, ). While many quantitative studies, even though they use a multifaceted theoretical lens, can be categorized based upon Rest's () ethical decision‐making framework, qualitative studies have been about exploring the ethical decision‐making framework beyond the Awareness – Judgment – Intention – Behavior model.…”
Section: Discussion Conclusion and Future Researchmentioning
confidence: 99%
“…Next, each Japanese corporation has its own main Japanese bank, traders, affiliated companies, and established customers (Tsalikis, & Seaton, 2007;Wagner-Tsukamoto, 2009). When the Japanese corporation's board members or executives belong to business associations such as Nihon Jidousha Kogyo Kai (Japanese Automobile Manufacturers Association), Keidairen (Japan Business Federation), Doyukai (Japan Association of Corporate Executives) and so on, other members from business associations may comprise of the close circle of that corporation (Davies, 2016;Davies & Ikeno, 2002;Mente, 1994;Mente, 2015;Tsalikis, & Seaton, 2007;Wagner-Tsukamoto, 2009).…”
Section: Japanese Corporationsmentioning
confidence: 99%
“…Wagner-Tsukamoto (2009) found that consumer perceptions and satisfactions, especially in the areas of product quality and safety are the prime drives, of the Japanese firms’ CSP. This study also found several dilemmas faced by Japanese firms when dealing with not-so-well-documented CSP practices and stressed that the implementation of environmental management systems as a fulfilment of CSP commitments is an outcome of those dilemmas.…”
Section: Corporate Social Performance In Japanmentioning
confidence: 99%